Grammar Express Unleashed: A Microlearning Hub Approach to Least Learned English 7 Competencies - Cunanan, Maica Angelou G. (Future Science / FSH-PH Publications, 2024)
The study employed a mixed-method developmental approach to design a learning hub imbued with microlearning to address the least learned competencies in English 7. The least learned competencies were identified by considering existing test results in the locale of the researcher, which were supported by the findings of existing studies in the literature through a systematic review. The researcher assumed the roles of content creator and curator and identified relevant microlearning materials available for access. Experts validated the quality of the identified learning content through an adopted questionnaire. Afterwards, the researcher designed the Grammar Express. ICT experts were asked to validate the platform using an adapted rubric to determine whether it is suitable as a learning website. An adapted questionnaire was used to measure the level of acceptance of Grammar Express by language teachers. Meanwhile, an adapted questionnaire was used to evaluate the level of usability of the platform as perceived by the students. Based on the findings, the respondents believe that Grammar Express is useful since it offers tangible benefits and can enhance instruction. Similarly, in terms of perceived ease of use, Grammar Express requires less effort to learn and utilize. In addition, there is a strong positive attitude to incorporate Grammar Express in language teaching. Furthermore, there is a strong intention to use Grammar Express, which indicates a high level of acceptance and enthusiasm for the platform. In terms of usability, there is a strong inclination toward frequent use and displayed confidence in navigating the platform independently.